A Sr and Nd isotopic study of five Yamato polymict eucrites and a comparison to other Antarctic and ordinary eucrites - Wooden, J.L.; Takeda, Hiroshi; Nyquist, L.E.; Wiesmann, H.; Bansal, B. (1983)
P(論文) Sr and Nd isotopic analysis of five Yamato polymict eucrites indicate that these samples formed at about 4.6 Ga ago with initial Sr and Nd ratios essentially the same as the analyzed non-Antarctic eucrites. The Yamato eucrites have Sr, Sm, and Nd concentrations that consistently lie among the highest found in eucritic samples. This characteristic identifies these Yamato samples as a closely related group. Comparisons between these Yamato samples and other Antarctic polymict eucrites clearly establishes that they all share some characteristic trace element features. Comparisons of Antarctic polymict eucrites with non-Antarctic ordinary eucrites reveal consistent differences. The most obvious is an enrichment of Rb in the polymict eucrites. These comparisons suggest that the Antarctic polymict eucrites belong to a single large family of material that is itself fairly diverse and distinct from the non-Antarctic eucrites. departmental bulletin paper